2023
DOI: 10.1007/s11033-023-08344-1
|View full text |Cite
|
Sign up to set email alerts
|

miR-122 dysregulation is associated with type 2 diabetes mellitus-induced dyslipidemia and hyperglycemia independently of its rs17669 variant

Abstract: Background: miR-122 is a liver speci c micro RNA that participates in the regulation of carbohydrate and lipid metabolism. rs17669 variant positioned at the anking region of miR-122 and may be affects its stability and maturation. Therefore, this study was aimed to investigates the association between rs17669 polymorphism with the miR-122 circulating level, risk of type 2 diabetes mellitus (T2DM) development and biochemical parameters in these patients and matched healthy controls.Methods and Results: Two hund… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…Consistent with our findings, Abnoos Mokhtari Ardekani et al indicate that miR-122 expression level in type 2 diabetes mellitus (T2DM) patients is significantly higher than that in control subjects. 36 Moreover, miR-122 is a potential novel tool for the early diagnosis and risk estimation of non-alcoholic fatty liver disease in T2DM patients. 37 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consistent with our findings, Abnoos Mokhtari Ardekani et al indicate that miR-122 expression level in type 2 diabetes mellitus (T2DM) patients is significantly higher than that in control subjects. 36 Moreover, miR-122 is a potential novel tool for the early diagnosis and risk estimation of non-alcoholic fatty liver disease in T2DM patients. 37 …”
Section: Discussionmentioning
confidence: 99%
“…Consistent with our findings, Abnoos Mokhtari Ardekani et al indicate that miR-122 expression level in type 2 diabetes mellitus (T2DM) patients is significantly higher than that in control subjects. 36 Moreover, miR-122 is a potential novel tool for the early diagnosis and risk estimation of non-alcoholic fatty liver disease in T2DM patients. 37 In addition, the outcomes of this study demonstrated that the total incidence of adverse pregnancy outcomes in the RG was significantly higher than the CG, and the levels of miR-122 and VEGF in the poor outcome group were elevated relative to the good outcome group.…”
Section: Discussionmentioning
confidence: 99%